2-Iodo-4 '-Methoxychalcone Attenuates Methylglyoxal-Induced Neurotoxicity by Activation of GLP-1 Receptor and Enhancement of Neurotrophic Signal, Antioxidant Defense and Glyoxalase Pathway - Tseng Yu-Ting (MOLECULES, 2019)
Methylglyoxal (MG) acts as a reactive precursor of advanced glycation end products (AGEs). This compound is often connected with pathologies such as diabetes, neurodegenerative processes and diseases of aging. 2-iodo-4 '-methoxychalcone (CHA79), a synthetic halogen-containing chalcone derivative, has been reported its anti-diabetic activity. This study aims to investigate the potential protective capability of CHA79 against MG-mediated neurotoxicity in SH-SY5Y cells. Results indicated CHA79 increased viability of cells and attenuated the rate of apoptosis in MG-exposed SH-SY5Y. CHA79 up-regulated expression of anti-apoptotic protein (Bcl-2) and down-regulated apoptotic proteins (Bax, cytochrome c, caspase-3, caspase-9). Moreover, CHA79 significantly up-regulated expression of neurotrophic factors, including glucagon-like peptide-1 receptor (GLP-1R), brain derived neurotrophic factor (BDNF), p75NTR, p-TrkB, p-Akt, p-GK-3 beta and p-CREB. CHA79 attenuated MG-induced ROS production and enhanced the antioxidant defense including nuclear factor erythroid 2-related factor 2 (Nrf2), HO-1, SOD and GSH. Furthermore, CHA79 attenuated MG-induced reduction of glyoxalase-1 (GLO-1), a vital enzyme on removing AGE precursors. In conclusion, CHA79 is the first novel synthetic chalcone possessing the GLP-1R and GLO-1 activating properties. CHA 79 also exhibits neuroprotective effects against MG toxicity by enhancing neurotrophic signal, antioxidant defense and anti-apoptosis pathway.